PENERAPAN METODE PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR GEOGRAFI SMA NEGERI 5 SURAKARTA TAHUN AJARAN 2012/2013 - Noviati, Noviati (Pendidikan Geografi, 2013)
The objective of this research were (1) To find out the improvement of learning achievement in basic competency of describing living environment conservation in relation to sustainable development using STAD learning method. (2)To find out the improvement of the students? geography learning achievement in the basic competency of describing living environment conservation in relation to sustainable development using STAD learning method. This study was a Classroom Action Research (CAR). The research was conducted in two sicluss. Each siclus consisted of determining the problem focus, planning, acting, monitoring, analyzing and reflecting. The subject of research was the XI IPS 2 Graders of SMA Negeri 5 Surakarta, consisting of 30 students. The data source derived from learning process in the classroom, result of evaluation test in siclus I, result of evaluation test in second siclus, geography learning motivation questionnaire of siclus I, geography learning motivation questionnaire of second siclus, and secondary data. Technique of collecting data employed were observation, document study, geography learning achievement test, and geography learning motivation questionnaire. The procedure of research used was self-reflection spiral model. The result of research showed: (1) the learning using Student Teams Achievement Divisions method could improve the geography learning motivation in the basic competency of describing living environment conservation in relation to sustainable development in second siclus. (2) The learning using Student Teams Achievement Divisions could improve the geography learning achievement in the basic competency of describing living environment conservation in relation to sustainable development in second siclus. Kata Kunci: Penelitian Tindakan Kelas, Student Teams Achievement Divisions, motivasi belajar geografi, hasil belajar geografi